Investigating the Impact of E-Portfolios on English Vocabulary Learning among Iranian EFL Learners: Focusing on Motivation and Attitude - Samir Alekasir; Azizollah Arvin; Malihe Charkhab (Shahid Chamran University of Ahvaz, 2022)
Purpose: The current study was conducted to investigate the effect of using electronic portfolios on learning English vocabulary with emphasis on the motivation and attitude of language learners in Ahvaz.Method: The research method used in the present study was quasi-experimental. The statistical population in this study included all 180 language learners studying English at the Iranian Language Institute (ILI), Khuzestan branch, who were learning their foreign language during the year 2020. Using the Morgan table, the sample size of 100 individuals was selected to take part in the study as participants. Then the learners were divided into two groups of 50 members (experimental and control groups) by simple random sampling. In order to tap the motivation variable in this study, the Scientific Motivation Questionnaire (SMQ), the Learner-Student Questionnaire (LLSQ), and the Experience Attitude and Feedback Questionnaire (AEFQ) were utilized. Additionally, to assess the rate of English vocabulary learning by learners, the researcher administered a pre-test and post-test. The reliability of the test was calculated using the KR-21 formula, and its validity was determined by three English experts. First, the Kolmogorov-Smirnov test was used to check the normality of the data of research variables, then using SPSS software and descriptive statistics (including tables, graphs, and means) and inferential statistics (including paired and independent t-tests) were calculated to analyze the gathered data. A qualitative analysis was administered to tap the data retrieved from the questionnaire.Findings: The findings of the present study showed that students who received their educational content through e-portfolios and were evaluated using e-portfolios had performed better in the post-test compared to their pre-test. Accordingly, it can be concluded that the implementation of e-portfolios in the learning environment could have a positive impact on developing the students' vocabulary knowledge and motivation of average Iranian EFL learners compared to traditional teaching and assessment methods.Conclusion: Finally, based on the research data, it can be concluded that when learning and formative assessment are combined in the educational environment, the evaluation tool becomes a kind of learning tool that helps students to improve their vocabulary knowledge.